Phylogeography and hybrid swarms : history of brackish water bivalve diversity in North European marginal seas - Nikula, Raisa (Helsingin yliopisto, 2010)
This study addressed the large-scale molecular zoogeography in two brackish water bivalve molluscs, Macoma balthica and Cerastoderma glaucum, and genetic signatures of the postglacial colonization of Northern Europe by them. The traditional view poses that M. balthica in the Baltic, White and Barents seas (i.e. marginal seas) represent direct postglacial descendants of the adjacent Northeast Atlantic populations, but this has recently been challenged by observations of close genetic affinities between these marginal populations and those of the Northeast Pacific. The primary aim of the thesis was to verify, quantify and characterize the Pacific genetic contribution across North European populations of M. balthica and to resolve the phylogeographic histories of the two bivalve taxa in range-wide studies using information from mitochondrial DNA (mtDNA) and nuclear allozyme polymorphisms. The presence of recent Pacific genetic influence in M. balthica of the Baltic, White and Barents seas, along with an Atlantic element, was confirmed by mtDNA sequence data. On a broader temporal and geographical scale, altogether four independent trans-Arctic invasions of Macoma from the Pacific since the Miocene seem to have been involved in generating the current North Atlantic lineage diversity. The latest trans-Arctic invasion that affected the current Baltic, White and Barents Sea populations probably took place in the early post-glacial. The nuclear genetic compositions of these marginal sea populations are intermediate between those of pure Pacific and Atlantic subspecies. In the marginal sea populations of mixed ancestry (Barents, White and Northern Baltic seas), the Pacific and Atlantic components are now randomly associated in the genomes of individual clams, which indicates both pervasive historical interbreeding between the previously long-isolated lineages (subspecies), and current isolation of these populations from the adjacent pure Atlantic populations. These mixed populations can be characterized as ...